Increased Cell Proliferation and Mucocyte Density in the Sea Anemone Aiptasia pallida Recovering from Bleaching - Fransolet, David (Public Library of Science, 2013)
Recovery of coral after bleaching episodes is a critical period for the health of the reef ecosystem. While events such as symbiont (genus Symbiodinium) shifting/shuffling or tissue apoptosis have been demonstrated to occur following bleaching, little is known concerning tissue recovery or cell proliferation. Here, we studied the sea anemone Aiptasia pallida exposed to a transient elevation of water temperature combined with high illumination (33°C and 1900 µmolphotons.m(−2).s(−1) for 30h). Following such treatment bleached anemones showed a significant reduction of their Symbiodinium density. Cell proliferation in the ectodermis and gastrodermis was determined by assessing the densities of cells labeled with a thymidine analogue (EdU). Cell proliferation significantly increased during the first day following stress in both tissue types. This increased cell proliferation returned to pre-stress values after one week. Although cell proliferation was higher in the ectodermis in absence of stress, it was relatively more pronounced in the gastrodermis of stressed anemones. In addition, the ratio of ectodermal mucocytes significantly increased three weeks after induced stress. These results suggest that thermal/photic stress coupled with the loss of the symbionts is able to enhance cell proliferation in both gastrodermis and ectodermis of cnidarians. While new cells formed in the gastrodermis are likely to host new Symbiodinium, the fate of new cells in the ectodermis was only partially revealed. Some new ectodermal cells may, in part, contribute to the increased number of mucocytes which could eventually help strengthen the heterotrophic state until restoration of the symbiosis.